Reply to "Comment on An Interesting Case Where Water Behaves as a Unique Solvent. 4-Aminophthalimide Emission Profile to Monitor Aqueous Environment " - Lissi-Gervaso, E; Abuin-Saccomano, E (American Chemical Society, 2013)
Sin Resumen Disponible